The Royal Wulff murders - McCafferty, Keith (McCafferty, Keith. Sean Stranahan mystery, 2012)
Sheriff Martha Ettinger investigates the suspected murder of a young man retrieved from the Madison River in Montana with a trout fly stuck in his lip.